Protective Effect of Adenosine A2B Receptor Agonist, BAY60-6583, Against Transient Focal Brain Ischemia in Rat - Dettori, Ilaria; Gaviano, Lisa; Ugolini, Filippo; Lana, Daniele; Bulli, Irene; Magni, Giada; Rossi, Francesca; Giovannini, Maria Grazia; Pedata, Felicita (Frontiers in Pharmacology, 2021)
Cerebral ischemia is a multifactorial pathology characterized first by an acute injury, due to excitotoxicity, followed by a secondary brain injury that develops hours to days after ischemia. During ischemia, adenosine acts as an endogenous neuroprotectant. Few studies have investigated the role of A2B receptor in brain ischemia because of the low potency of adenosine for it and the few selective ligands developed so far. A2B receptors are scarcely but widely distributed in the brain on neurons, glial and endothelial cells and on hematopoietic cells, lymphocytes and neutrophils, where they exert mainly anti-inflammatory effects, inhibiting vascular adhesion and inflammatory cells migration. Aim of this work was to verify whether chronic administration of the A2B agonist, BAY60-6583 (0.1 mg/kg i.p., twice/day), starting 4 h after focal ischemia induced by transient (1 h) Middle Cerebral Artery occlusion (tMCAo) in the rat, was protective after the ischemic insult. BAY60-6583 improved the neurological deficit up to 7 days after tMCAo. Seven days after ischemia BAY60-6583 reduced significantly the ischemic brain damage in cortex and striatum, counteracted ischemia-induced neuronal death, reduced microglia activation and astrocytes alteration. Moreover, it decreased the expression of TNF-α and increased that of IL-10 in peripheral plasma. Two days after ischemia BAY60-6583 reduced blood cell infiltration in the ischemic cortex. The present study indicates that A2B receptors stimulation can attenuate the neuroinflammation that develops after ischemia, suggesting that A2B receptors may represent a new interesting pharmacological target to protect from degeneration after brain ischemia.